Aplikasi Pendekatan Interdisipliner dalam Studi Hukum Perkawinan - Rianti; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
This research examines the application of an interdisciplinary approach in the study of marriage law, with a focus on integration between the disciplines of law, sociology and anthropology. This interdisciplinary approach aims to provide a more comprehensive and holistic understanding of marriage legal issues, which often cannot be resolved adequately through a legal perspective alone. The research results show that an interdisciplinary approach is able to enrich understanding of marriage legal issues, such as divorce, domestic violence, and the rights and obligations of husband and wife, by taking into account socio-cultural dynamics and individual psychological aspects in marriage. This approach also supports the formulation of marriage policies that are more inclusive, fair and sustainable, as well as increasing the effectiveness of law enforcement. This study concludes that an interdisciplinary approach is very relevant in facing modern challenges in the field of marriage law and can be the basis for developing policies that are more adaptive to society's needs.